Vienna Conventions on the Law of Treaties : a commentary Volume II - Corten, Olivier; Klein, Pierre, 1964- (Oxford ; New York : Oxford University Press, 2011)
The 1969 and 1986 Vienna Conventions on the Law of Treaties are essential components of the international legal order. This is a commentary on their provisions, containing thorough and well-structured analyses of each of their articles.
V. 1.: Introduction -- Conclusion and entry into force of treaties -- Observance, application and interpretation of treaties -- v. 2.: Amendment and modification of treaties -- Invalidity, termination and suspension of the operation of treaties -- Miscellaneous provisions -- Depositaries, notifications, corrections and registration -- Final provisions.
Includes bibliographical references and index.
Keywords: Vienna Convention on the Law of Treaties -- (1969 May 23); Vienna Convention on the Law of Treaties between States and International Organizations or between International Organizations -- (1986); Vienna Convention on the Law of Treaties -- Studies; Vienna Convention on the Law of Treaties (1969 May 23); Vienna Convention on the Law of Treaties between States and International Organizations or between International Organizations (1986); Treaties; Traites; Treaties; Droit international public; Conventions internationales; Commentaires; Treaties; Treaties; Treaties